Rheological and mechanical properties of hot mix asphalt incorporating polypropylene and polyethylene fibers - Ferdaus, R.; K. A., Masri; Putra Jaya, Ramadhansyah; Md. Shahnewaz, Shoaib (Trans Tech Publications Ltd, 2023)
Polymer-modified binders in hot mix asphalt (HMA) mixtures have become more widely used in recent years. To prevent fatigue, rutting and various distresses, different types of polymer modifiers have been utilized. This study investigates modifying asphalt mixture in dense asphalt mixture with polypropylene (PP) and polyethylene (PE) fibers. The performance test includes softening point, penetration test as physical properties, and dynamic creep test for mechanical behavior of modified asphalt mixtures incorporating PP, PE, and unmodified asphalt. The PP and PE fiber dosage adopted for this study was 0.5% - 2.5% by weight of the asphalt. The results of the study are that the effect of polypropylene and polyethylene fibers on asphalt mixture behavior is sensibly good from considering rheological and mechanical properties. In the physical property test, it was found that PE-modified asphalt offers a better blend in comparison to PP-modified asphalt. In the dynamic creep test, for 2% of PP and 1.5% of PE modified asphalt showed the highest resistance and lowest strain value than unmodified asphalt mixtures.